2000
DOI: 10.1002/etc.5620191005
|View full text |Cite
|
Sign up to set email alerts
|

Spiking hydrophobic organic compounds into soil and sediment: A review and critique of adopted procedures

Abstract: Abstract-Studies on the fate and effects of organic pollutants in soil and sediment are often carried out under laboratory conditions and often require the study compound to be introduced, or spiked, into the test substrate. The procedures adopted to spike relatively large amounts of hydrophobic organic compounds into soil and sediment can introduce interferences into experiments that have the potential to dominate the process(es) under investigation. This review identifies and discusses key factors of spiking… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
45
0

Year Published

2000
2000
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 85 publications
(45 citation statements)
references
References 141 publications
0
45
0
Order By: Relevance
“…Water-immiscible solvents have been used as carriers to spike organic chemicals into wet soil and sediment. However, because they do not dissipate as effectively in the presence of water, the homogeneity of spike distribution may be poor [18].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Water-immiscible solvents have been used as carriers to spike organic chemicals into wet soil and sediment. However, because they do not dissipate as effectively in the presence of water, the homogeneity of spike distribution may be poor [18].…”
Section: Methodsmentioning
confidence: 99%
“…We have identified soil and sediment drying and rewetting, carrier solvent persistence, and spike homogeneity as three key factors that can significantly influence experiments and that should be considered when developing or using a spiking procedure. These three factors and others we identified led us to make a number of recommendations to follow when spiking organic compounds into soil and sediment [18].…”
Section: Introductionmentioning
confidence: 99%
“…The sediments were spiked following the procedure outlined by Northcott and Jones [22]. Namely, a 250 g sediments sample was spiked with a fixed volume of a PAH stock mixture and 10 mL acetone, in order to obtain a given contamination.…”
Section: Spiking Proceduresmentioning
confidence: 99%
“…For example, over 50% losses in total PHE and PYR were observed by (Šmídová et al, 2012;Obuekwe and Semple, 2013) in 56 or 63 days whilst less than 13% dissipation was reported by Hwang and Cutright (2002) C-analysis not only measures parent compounds but also degraded products whilst the GC/MS instrumental analysis only calculates parental compounds (Šmídová et al, 2012); (2) sterilisation: Contreras-Ramos et al (2006) reported that the reduction in PHE in natural soils aged for 11 weeks was as high as 88% but only 8-20% in sterile soils; (3) spiked concentrations: catabolic activities might be triggered when PAH concentrations were above threshold values (Macleod and Semple, 2000); and (4) spiking procedures including spiking method, carrier solvent, mixing, homogeneity and equilibrium: e.g. carrier solvent has the potential to affect organic matter in soils where the sorption of PAHs mainly takes place (Northcott and Jones, 2000). Based on the stability of concentrations in soils, PYR and B[a]P were chosen for interaction study with As, Cd and Pb.…”
Section: Temporal Change In Soil Pah Concentrationsmentioning
confidence: 99%